Effects of Employee”™s Commitment, Training and Supervision on the Implementation of the Occupational Health and Safety at PT Trans Marga Jateng Semarang - Andhani, Galuh Punjung; Taviyastuti, Taviyastuti -; Hasyim, Fatchun - (JOBS (Jurnal Of Business Studies), 2023)
The purpose of this research is to find out the influence of employee”™s commitment, training and supervision towards the implementation of The Occupational Health and Safety (OHS) at PT Trans Marga Central Java.This research is a quantitative research with sampling method is purposive sampling. This research is use data analysis method multiple linear regression analysis technique.The result showed that commitment and training have a positive and significant relationship with the implementation of The Occupational Health and Safety (OHS) meanwhile supervision partially has no significant relationship on the implementation of The Occupational Health and Safety (OHS). Simultaneously commitment, training and supervision have a positive and significant relationship with The implementation of The Occupational Health and Safety (OHS). The coefficient of determination in this research is 0,737 which means that 73,3% implementation of The Occupational Health and Safety (OHS) is influenced by commitment, training and supervision.